Periodontal Disease: A Predictive Profile - AL-Mafraji, F. H.; Alaubydi, M. A. (Iraqi Journal of Science, 2023)
Periodontal diseases such as gingivitis and periodontitis are considered common diseases. This study is aimed to predicate these diseases using non-harmful specimens such as saliva throughout the detection of some parameters. In the beginning, a random 51 patients' saliva was collected from outpatients who suffered from different degrees of periodontal diseases. Concurrently, another 40 people who appeared to be healthy were collected, and both patients and healthy people were subjected to a questionnaire form and diagnosed by a specialist dentist. The results of this study revealed that there is no significant difference between males and females in infection with periodontal diseases. As well, smoking is not acting as the main factor causing this disease. Most patients' saliva pH was acidic. Immunological parameters such as toll-like receptor 2 (7.384  ±  4.031,5.313  ±  3.106 ng/ml) and α- amylase(2.444  ±  1.870,1.041  ±  1.044 ng/ml) are both increased significantly in patients than in the control group respectively, with no significant differences for CRP between both experimental groups, which may have been used both TLR2 and alpha-amylase with acidic pH as biomarkers to detect periodontal diseases.